Answer:
The picture shows the answer on the graph
Step-by-step explanation:
-2=-3/4×(x-6)
Distribute -3/4 through the parenthesis
-2= -3/4x+9/2
Multiply both sides of the equation by 4
-8=-3x+18
Move the variable to the left side and change its sign
3x-8=18
Move constant to the right side and change its sign
3x=18+8
Add the numbers
3x=26
Divide both sides of the equation by 3
x=26/3
Alternative Form- x=8 2/3 or x=8.6
Answer:
i think C. if i am right tell me
Step-by-step explanation:
Answer:
52
Step-by-step explanation:
plug in 3 if we're going by 0,1,2,3
2+ (3-1)25
2+50
52
- f (x) = 3x² + x
- Find f (-5).
Given,
Now, we have to find f (-5). To find this, we just need to substitute -5 in the place of x.
So,